Immobilization of Antioxidant Enzyme Catalase on Porous Hybrid Microparticles of Vaterite with Mucin - Balabushevich, Nadezhda G.; Kovalenko, Ekaterina A.; Maltseva, Liliya N.; Filatova, Lyubov Yu; Moysenovich, Anastasia M.; Mikhalchik, Elena; Volodkin, Dmitry; Vikulina, Anna (Advanced Engineering Materials, 2022)
Catalase is one of the crucial antioxidant enzymes with diverse applications in textile, food industries, wastewater treatment, cosmetics, and pharmaceutics, which, however, is highly sensitive to environmental challenges. Resisting the loss of activity and prolongation of formulation storage can be achieved via the catalase entrapment into insoluble carriers. Affordable and degradable vaterite is proposed as amicable material for catalase immobilization. To improve the carrier properties of the vaterite, it was co-precipitated with mucin from the pig's stomach producing ca 5 μm hybrid mucin/vaterite microparticles. Catalase is impregnated into the crystals by means of adsorption without chemical modifications. The presence of mucin matrix partially hinders catalase penetration into the crystals and reduces the adsorption capacity (for 0.1 mg mL−1 catalase, ca 2.3 vs ca 1.5 mg g−1 for pristine and hybrid microparticles, respectively) but significantly promotes the protection of antioxidant activity upon storage and under the action of temperature, organic solvent (acetonitrile), and proteolytic enzyme (trypsin). Hybrid microcrystals are pH-sensitive and better retain the enzyme at pH 3–5 due to catalase-mucin complexation. Immobilized catalase can be used for 5–6 consecutive cycles until it loses catalytic activity. Altogether, these findings indicate promises of hybrid mucin/vaterite microparticles for immobilization of antioxidant enzymes.
CRIS-Team Scopus Importer:2022-05-13
Keywords: adsorption; antioxidant enzyme; catalase; drug carrier; mucosal delivery